Pengembangan Instrumen Asesmen Diagnostik Kognitif Berbasis Android dan Desktop pada Pembelajaran IPA Kelas VIII SMP Daruttaqwa Jombang - Qurtubi, Imam Ahmad; Hakim, Miftahul; Afandi, Benny (Jurnal Pendidikan Biologi Undiksha, 2023)
This research aims to determine the product development process, product feasibility, and user response to the product. This type of research is Research and Development using steps according to Sugiyono. The instrument development process consists of several stages, namely preparing all supporting aspects of application creation and design, the assessment question design stage, and the application design stage. The validation carried out is media and material validation by distributing validation questionnaires. The trials carried out were product trials and usage trials, product trials were carried out by 3 class IX students and science teachers, while usage trials were carried out by 15 class VIII students and science teachers. The trial location is located at Daruttaqwa Junior High School, Jombang District, Jember Regency. The results of the research were, product development produced Android and Desktop Based Cognitive Diagnostic Assessment Instruments for Science Learning at Daruttaqwa Jombang Junior High School, media suitability validation was 86.66%, material suitability validation was 76.66%, student responses to product trials were 86.66%. 88.33%, teacher response in product trials was 90%, student responses in usage trials were 90.5%, and teacher responses in usage trials were 87.5%. Product quality determination uses minimum assessment criteria which are included in the "Decent" category with a percentage ≥ 56%. Based on these provisions, Android and desktop based cognitive diagnostic assessment instruments are suitable for use in implementing cognitive diagnostic assessments of science learning at Daruttaqwa Junior High School, Jombang.